The effect of compound Kehon exercises in the development of the Agility of Kyokushinkai Karate elite players - Tariq, Uoday (Journal of Physical Education, 2016)
Through researcher experience being the head of the Iraqi Union and the Asian Kyokushinkai Karate and Chairman of the Technical Committee, meat that the Iraqi player leads a lot of offensive skills of various kinds, it lacked the correct timing as well as speed, diversity and here felt researcher going into this problem through training compound Kehon and learn the effect of these exercises in the development of research and agility own goal to identify the impact of the exercises Kehon compound in the development of motor fitness of the research sample, the researcher assumed that there are significant differences between tribal and dimensional tests of a sample search results in fitness choices kinetic differences. Due to the nature of the problem, the experimental method is the best curriculum that can be used in dealing with the problem of current research, the researcher chose intentional sample consisted my players elite applicants numbering 22 players, and the dimension of a tribal tests and then apply the curriculum kehon training compound and then hold the post tests researcher concluded that classic exercises known in the sport of Kyokushinkai Karate have had a positive impact on some of the general motor abilities such as agility and also concluded that the use of compound exercises Kehon is an excellent way to develop public and private motor capacity. And in particular the development of agility own, and recommended researcher conducting other studies and other samples to identify the effect of compound exercises Alkihwn in the development of physical and motor abilities and skills as well as an emphasis on the development of agility very important tool in achieving positive results in the sport of Kyokushinkai Karate